Transparency of assessment decision-making when students are not meeting required levels of proficiency in clinical practice. (February 2020) - Cassidy, Simon; Coffey, Michael; Murphy, Fiona
Abstract: This paper discusses the context of assessing nursing and midwifery students who are not meeting required levels of proficiency in clinical practice. The paper then outlines an action plan protocol designed to assist supervisors and assessors examine the credibility of their assessment decisions in these circumstances. Development of the protocol draws on a comprehensive review of evidence and original research showing the personal, professional and organizational pressures faced when a student is failing to achieve proficiency in clinical practice. The action plan protocol is suggested as one way of addressing the need to document concerns to enable students to ultimately self-regulate their learning and professional development. Highlights: Assessment accountability is key to gatekeeping healthcare professions. Responding to students not meeting required levels of proficiency is vital to professional standards. Assessment decision-making must meet criteria of fairness and transparency. Action planning is key to ensuring specific areas of concern are recognised. Constructive feedback provides opportunities for self-regulation of students' practice.